Effectiveness and Safety of Different Patch Materials for Supravalvar Aortic Stenosis (Middle-Term Outcomes) - Xinyue Lang; Lizhi Lv; Simeng Zhang; Aihua Zhi; Cheng Wang; Qiang Wang (Reviews in Cardiovascular Medicine, 2024)
Background: To determine the effectiveness and safety of different patch materials in the treatment of pediatric patients with congenital supravalvular aortic stenosis (SVAS). Methods: 218 consecutive SVAS patients (age <14 years) who underwent surgery from Beijing Fuwai and Yunnan Fuwai hospital between 2002 and 2020 were included. Patients were divided into the pericardium patch group (133 (61.0%)), modified patch group (43 (19.7%)) and artificial patch group (42 (19.3%)). The primary safety endpoint was patch-related adverse complications (post-operation patch hemorrhage or aortic sinus aneurysm at 2-year follow-up). The primary effectiveness outcome was the re-operation or restenosis at 2-year follow-up. Multivariable cox regression was used to obtain the hazard ratio (HR). Results: The median age at operation was 43.5 months (IQR 24.0–73.0). Only three patients had patch-related adverse complications, and no difference existed among the three groups (p = 0.763). After a median follow-up of 24.0 months (IQR 6.0–48.0), patients with a pericardium patch had a lower re-operation or restenosis rate compared with the other two groups (pericardium patch vs modified patch, HR = 0.30, 95% CI 0.12–0.77; pericardium patch vs artificial patch, HR = 0.33, 95% CI 0.13–0.82), even in the main subgroup and sensitivity analysis. Conclusions: In pediatric patients, the safety of autologous pericardium patch is acceptable, along with lower rates of middle-term re-operation or restenosis. Clinical Trial Registration: http://www.chictr.org.cn, number: ChiCTR2300067851.